MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF - Sandi, Qalka; Syukri, Ahmad; Anwar US, Kasful (Al Ghazali, 2019)
In the development of the Indonesian nation, every effort is aimed at improving the quality of human resources, which means that people are central to national development and as an effort to increase competitiveness in the global market. Effective management of human resources (HR) must be considered in order to support the strategies that will be applied in order to contribute in creating competitive advantage in an organization. Competitive advantage can be created through effective human resource management by taking into account internal and external factors of the organization / educational institution that will be confronted. In addition, competitive human resources need to be supported by several elements, namely strategy in human resource management, organizational resources, and organizational strategy. The discussion of this study regarding; First, the concept of Human Resource Management which discusses the design or ideas, understanding and functions of human resource management. Second, Competitive Advantage in Human Resources, which is about the ability obtained through the characteristics and resources of a person, to have higher performance compared to other educational organizations / institutions in the same industry or market. Third, Management of Human Resources in Improving Competitive Advantage, namely regarding management strategies to achieve competitive advantage in human resources.